Análise de lucratividade e rentabilidade em lojas física e virtual - Santos, Estela Rosso dos (2024)
Nowadays, online sales have grown a lot and physical stores are possibly no longer selling, as they commonly sold in the period when the technological transformation had not occurred (COUTINHO et al., 2017). With these variations in sales, profitability appears in different ways. Therefore, it is valuable to understand how this event impacts the company's profitability. Every day more consumers are looking for convenience and ease, so business owners end up adapting and meeting the “wants” of their customers (COUTINHO et al., 2017). According to research by Octadesk (2023), 61% of Brazilians choose to shop in e-commerce. Thus, it can be said that, on average, three out of every five people acquire something online. Furthermore, according to this research, the report showed that price and practicality were the main factors driving online retail, as 73% of respondents stated that in online stores it is possible to find lower prices than in physical stores.